Psychodynamic Perspective of Organizational Change = Zmiana organizacyjna w ujęciu psychodynamicznym - Barabasz, Adela (Zielona Góra: Faculty of Economics and Management Press)
The complex processes and phenomena that are taking place in the contemporary world require new and adequate methods of acting also in the area of management. This means the need for a fresh approach to the process of organization development and change. This paper presents the key concepts stemming from the psychoanalytic approach to organization and management.
Keywords: zarządzanie; organizacja; podejście psychodynamiczne; zmiana organizacyjna; emocje; mechanizmy obronne; kadra menedżerska; management; organization; psychodynamic approach; organizational change; emotions; defence mechanisms; managers